Questionnaire design and data analysis: An alternative approach in student evaluation of teaching (SET) - Lim, Tick Meng; Chiam, Chooi Chea; Phang, Siew Nooi * (Sunway University, 2012)
Student evaluation of teaching (SET) has been widely used in institutions of learning to assess teaching effectiveness. However, most of the SET questionnaires are designed by “experts” without taking students’ view into consideration. Besides that, the traditional approach in SET analysis is to obtain a global rating as a measurement of teaching effectiveness based on the average or mean scores of the items of SET. This paper identifies the weaknesses of the traditional approach in SET questionnaire development and data analysis. It then describes an alternative approach to SET items development which involved students- collaboration. The paper also describes the establishment of various scoring matrices for the measurement of overall teaching effectiveness as well as teaching effectiveness from three different domains, namely: knowledge, pedagogical skills and attitude